Self-Serving Use of Equity Rules in Bargaining with Asymmetric Outside Options - Bernd Irlenbusch; Heike Hennig-Schmidt; Rainer Rilke; Gari Walkowitz (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
We experimentally investigate the relevance of (asymmetric) outside options in ultimatum bargaining. Building on the generalized equity principle formulated by Selten (1978) we derive three di erent equity rules. These equity rules can explain 43% of all o ers. Our within-subject design allows us to show that proposers apply the equity rules in a self-serving manner, i.e., proposers tend to follow the rules that suggest the highest payo for them. This tendency leads to high ine ciencies due to frequent rejections.
Keywords: C78; C91; D63; 330